Arylpyrrole and fipronil analogues that inhibit the motility and/or development of Haemonchus contortus in vitro. Issue 3 (December 2018) - Dilrukshi Herath, H.M.P.; Song, Hongjian; Preston, Sarah; Jabbar, Abdul; Wang, Tao; McGee, Sean L.; Hofmann, Andreas; Garcia-Bustos, Jose; Chang, Bill C.H.; Koehler, Anson V.; Liu, Yuxiu; Ma, Qiaoqiao; et al.
Abstract: Due to widespread drug resistance in parasitic nematodes, there is a need to develop new anthelmintics. Given the cost and time involved in developing a new drug, the repurposing of known chemicals can be a promising, alternative approach. In this context, we tested a library (n = 600) of natural product-inspired pesticide analogues against exsheathed third stage-larvae (xL3s) of Haemonchus contortus (barber's pole worm) using a whole-organism, phenotypic screening technique that measures the inhibition of motility and development in treated larvae. In the primary screen, we identified 32 active analogues derived from chemical scaffolds of arylpyrrole or fipronil. The seven most promising compounds, selected based on their anthelmintic activity and/or limited cytotoxicity, are arylpyrroles that reduced the motility of fourth-stage larvae (L4s) with significant potency (IC50 values ranged from 0.04 ± 0.01 μM to 4.25 ± 0.82 μM, and selectivity indices ranged from 10.6 to 412.5). Since the parent structures of the active compounds are uncouplers of oxidative phosphorylation, we tested the effect of selected analogues on oxygen consumption in xL3s using the Seahorse XF24 flux analyser. Larvae treated with the test compounds showed a significant increase in oxygen consumption compared with the untreated control, demonstrating their uncoupling activity. Overall, the results of the present study have identified natural product-derived molecules that are worth considering for chemical optimisation as anthelmintic drug leads. Graphical abstract: Image 1 Highlights: Pesticide analogues were assessed for anthelmintic activity. Inhibition of motility and development of larval stages of Haemonchus contortus . Uncoupling of oxidative phosphorylation in larvae.